Very low HIV positivity on paediatric surgical wards in Mozambique: Implications for inpatient provider-initiated testing programmes - Henriques Viola; Angela Bi; Dalva Khosa; Zacarias Mateus; Massada Da Rocha; Vanda Amado; Atanásio Taela; Daniel A. DeUgarte; Andreas Schindele; W. Chris Buck (Southern African Journal of HIV Medicine, 2024)
No abstract available.